What Did I Do? Practitioner Awareness of Ethical Issues in Scientific Publishing - Kennedy, LMT, BCTMB, DrPH, Ann Blair; Moraska, PhD, Albert; Rich, PhD, BCTMB, LMT, Grant (International Journal of Therapeutic Massage & Bodywork, 2017)
Massage therapy practice as well as research in massage therapy is guided by ethical principles and boundaries of professional behavior. Scientific publishing is also guided by a set of ethical standards, about which all aspiring scientific authors should be aware. Honesty, integrity, and conflicts of interest are issues in science and these issues can also impact scientific publishing. Historical ethical issues and current events are discussed.